The role of transverse occipital sulcus in scene perception and its relationship to object individuation in inferior intraparietal sulcus - Bettencourt, Katherine C. (2013)
The parietal cortex has been functionally divided into various subregions; however, very little is known about how these areas relate to each other. Two such regions are the transverse occipital sulcus (TOS) scene area and inferior intraparietal sulcus (IPS). TOS exhibits similar activation patterns to the scene selective parahippocampal place area (PPA), suggesting its role in scene perception. Inferior IPS, in contrast, has been shown to participate in object individuation and selection via location. Interestingly, both regions have been localized to the same general area of the brain. If these two were actually the same brain region, it would have important implications regarding these regions’ role in cognition. To explore this, we first localized TOS and inferior IPS in individual participants and examined the degree of overlap between these regions in each participant. We found that TOS showed only a minor degree of overlap with inferior IPS (∼10%). We then directly explored the role of TOS and inferior IPS in object individuation and scene perception by examining their responses to furnished rooms, empty rooms, isolated furniture, and multiple isolated objects. If TOS and inferior IPS were the same region, we would expect to see similar response patterns in both. Instead, the response of TOS was predominantly scene selective, while activity in inferior IPS was primarily driven by the number of objects present in the display, regardless of scene context. These results show that TOS and inferior IPS are nearby, but distinct regions, with different functional roles in visual cognition.